Analysis of the Potential Use of Selected Modes of Transport in the Courier Services Sector - Tumielewicz, Michał; Odważny, Emil (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of this chapter is to analyze the functioning of the CEP (courier, express, parcel) sector and assess its development potential through the application of modern logistic solutions. The study characterizes the courier market and identifies the key factors influencing the operational efficiency of logistics operators, with a particular focus on major players such as DHL, FedEx, UPS, and TNT. The analysis shows that growing competition in the CEP sector stimulates investment in new technologies, process automation, and service personalization. Special importance is given to the development of parcel tracking systems and delivery route optimization, which contribute to operational efficiency and improved customer service. The implementation of innovative solutions enables faster, safer, and more flexible deliveries, which are essential for building competitive advantage. The value of this chapter lies in emphasizing the role of technological innovation in shaping the future of the CEP sector and improving logistics processes.